Internalisasi Environmental Awareness dalam Mata Pelajaran IPA melalui Model Pembelajaran Radec pada Sekolah Dasar - Shofwatul Abidah; Langgeng Budianto; Ni’matuz Zuhroh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze in depth the process of internalizing Environmental Awareness (EA) in elementary school students through the implementation of the RADEC (Read, Answer, Discuss, Explain, Create) Learning Model in the Science Curriculum. The background of the problem is the gap between students' environmental knowledge (cognitive) and minimal daily pro-environmental actions (behavior). The study used a qualitative case study method implemented at SDNU Gurah Kediri. Data were collected through participant observation, in-depth interviews with teachers and key students, and analysis of student artifacts during the Create phase. The findings indicate that the RADEC Model is effective as a pedagogical vehicle that facilitates the internalization of EA by transforming passive awareness into active action. The strongest internalization mechanisms occur in the Discussion Phase, which encourages the strengthening of affective values ​​and social responsibility, and the Create Phase, which bridges science knowledge with conative behavior through the creation of concrete solutions (e.g., simple recycling or renewable energy projects). Significant improvements were found in the dimensions of students' attitudes and behaviors, where students began to view pro-environmental actions as a personal moral responsibility, not just a school assignment. It can be concluded that the RADEC Model provides a superior structured framework for simultaneously integrating science education and ecological character building in elementary schools.